Strategi Pembinaan oleh Kepala Sekolah Dalam Meningkatkan Kualitas Pendidikan - Sopiandy, Dede; Takwa, Takwa (GERAM: Gerakan Aktif Menulis, 2022)
This research objective to describe and analyze the Principal Coaching Strategies in improving the quality of education. This research was carried out in Private Aliyah Madrasa Al-Amin District Labokeo Southern Wowoni island with the informant's research is the principal and the teachers in the school. The approach used is descriptive qualitative in-depth interview by (deep interview) and documentation, to the informant as the primary data collection techniques. Through the technique of determination of informants in snowball obtained the main informant the principal and teachers at Private schools. While secondary data on Madrasah Aliyah documents obtained from the private Al-Amin Wowoni Island Regency, South Labokeo at the relevant point of view. The research result found that strategy done by a principal in improving education covering coaching academical or supervision academic covering design program of instruction, learning, carry out commitment to work, evaluate learning, during tutoring hours to students, manage class, using media and source of learning, as well as training discipline the teacher then administrative guidance management includes teaching, management kepegawaian, management student, management facilities and infrastructures, and financial management.